Effects of the Human SULT1A1 Polymorphisms on the Sulfation of Acetaminophen, O-Desmethylnaproxen, and Tapentadol - Rasool, Mohammed I. (Pharmacol Rep, 2018)
BACKGROUND: Non-opioid and opioid analgesics, as over-the-counter or prescribed medications, are widely used for the management of a diverse array of pathophysiological conditions. Previous studies have demonstrated the involvement of human cytosolic sulfotransferase (SULT) SULT1A1 in the sulfation of acetaminophen, O-desmethylnaproxen (O-DMN), and tapentadol. The current study was designed to investigate the impact of single nucleotide polymorphisms (SNPs) of the human SULT1A1 gene on the sulfation of these analgesic compounds by SULT1A1 allozymes. METHODS: Human SULT1A1 genotypes were identified by database search. cDNAs corresponding to nine SULT1A1 nonsynonymous missense coding SNPs (cSNPs) were generated by site-directed mutagenesis. Recombinant wild-type and SULT1A1 allozymes were bacterially expressed and affinity-purified. Purified SULT1A1 allozymes were analyzed for sulfation activity using an established assay procedure. RESULTS: Compared with the wild-type enzyme, SULT1A1 allozymes were shown to display differential sulfating activities toward three analgesic compounds, acetaminophen, O-desmethylnaproxen (O-DMN), and tapentadol, as well as the prototype substrate 4NP. CONCLUSION: Results obtained indicated clearly the impact of genetic polymorphisms on the drug-sulfation activity of SULT1A1 allozymes. Such information may contribute to a better understanding about the differential metabolism of acetaminophen, O-DMN, and tapentadol in individuals with different SULT1A1 genotypes.